Tinjauan Yuridis atas Pertanggungjawaban Pengurus Baitul Maal Wa Tamwil yang Tutup terhadap Simpanan Anggota - Abas, Saffana Zhafirah; Permata, Cahaya (AL-SULTHANIYAH, 2025)
The closure of Baitul Maal Wa Tamwil has given rise to many problems, including the return of member deposits. The purpose of this research is to examine the accountability of the management of BMT that closes regarding member deposits and the form of legal protection for member deposits in accordance with legislative regulations. As normative research, this study employs a statute approach and a conceptual approach. Data is collected through document studies, then processed and analyzed qualitatively to illustrate the obligations of the management and the rights of BMT members as parties entitled to their deposits. The results of this study indicate that the management is obliged to return the member deposit funds if the losses incurred are due to negligence or intentional actions by the cooperative management in accordance with the provisions of Article 34 paragraph (1) and paragraph (2) of Law no. 25 of 1992. and the members only bear losses to the extent of their principal savings, mandatory savings, and their ownership capital, therefore the members are entitled to protection in the form of guarantees for the return of their savings.